2021
DOI: 10.1039/d0ew01125h
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the feed composition and membrane wetting in a direct contact membrane distillation process

Abstract: Membrane distillation is a promising option for desalination owing to its advantages, but additional studies are still required before drawbacks such as membrane wetting can be resolved. To investigate the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…sults showed that although unsteady vortex structures are able to mix ization layers with the bulk, they are unable to mix the concentration spacers often increase the permeate flux at the expense of greater mine Lim et al [15] used a lab-scale DCMD system to investigate the e concentration of organic and inorganic contents in feed bulk on wettin Their results show that a salt concentration rise in the added solution i brane wetting. Moreover, salts could pass through wetted pores and fo on the distillate side of the membrane.…”
Section: Modeling and Configuration Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…sults showed that although unsteady vortex structures are able to mix ization layers with the bulk, they are unable to mix the concentration spacers often increase the permeate flux at the expense of greater mine Lim et al [15] used a lab-scale DCMD system to investigate the e concentration of organic and inorganic contents in feed bulk on wettin Their results show that a salt concentration rise in the added solution i brane wetting. Moreover, salts could pass through wetted pores and fo on the distillate side of the membrane.…”
Section: Modeling and Configuration Descriptionmentioning
confidence: 99%
“…Lim et al [ 15 ] used a lab-scale DCMD system to investigate the effect of varying the concentration of organic and inorganic contents in feed bulk on wetting membrane pores. Their results show that a salt concentration rise in the added solution increased the membrane wetting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precipitated minerals block the membrane pores and reduce the membrane’s water vapor permeability. Scaling by gypsum, silica, calcite, sodium chloride, and mixed salt feed solutions has been investigated. Among different types of scalants, gypsum is one of the most challenging and widely studied scalants due to its practical relevance and its low and pH-insensitive solubility, that is, scaling by gypsum cannot be mitigated by merely adjusting the pH of the feed solution as in the case of mitigating calcite scaling. ,, …”
Section: Introductionmentioning
confidence: 99%